Islamic Education Guidance for Elderly at Pertapis Senior Citizen and Fellowship Home (PSCFH) - Einon Bte Mohd Taib; Imas Kania Rahman (Prophetic guidance and counseling journal, 2022)
Maturity is not an indication of age but its development depends on the primary education in Islam nurtured since young. A person needs to equip themselves with religious knowledge to prepare them for the Day of Reckoning and it is found that not all elderly is as well equipped. As such, the objective of this article is to study how senior citizen at Pertapis Senior Citizen and Fellowship Home (PSCFH) are guided in their Islamic Education. The research was planned to be conducted in person at PSCFH through interviews, observation and documentation. However, the Covid-19 pandemic had affected the method due to Safety Management System, as an alternative, the research was conducted through phone interviews, video observation, information found from YouTube and websites as to collect all the relevant data. These are then analyzed using triangulation. It was found that in PSCFH had prioritized religious education guidance for the elderly. Alongside to this, the mission and vision by PSCFH is to provide psychological care towards health and wellness of the elderly, so as to benefit the elderly and not cause issues in the society. It is suggested that the religious education is supplemented with Fiqh studies concerning daily living other than reading the Al-Quran only. The elderly is encouraged to Zikir more as to strengthen faith to be closer to Allah and motivates them to be peaceful and independent. Abstrak         Kematangan sesaorang bukanlah bergantung kepada usia, tetapi perkembangan kematangan adalah dari latar belakang Pendidikan Ilmu agama yang diwarisi. Pengetahuan agama perlu diperoleh sebagai bekal diri untuk bertemu kepada Allah pada hari kebangkitan dan ternyata tidak semua warga tua yang memilikinya. Dengan demikian tujuan penulisan ini menyasarkan kepada warga tua usia lanjut untuk mendapatkan bimbingan Pendidikan Agama Islam di rumah kebajikan Muhibbah Warga Tua Pertapis. Penelitian seharusnya dilakukan secara penelitian lapangan melalui wawancara, observasi, dan dokumentasi, tetapi ketika penulisan ini untuk diselesaikan, dunia sedang mengalami wabah covid-19. Oleh yang demikian penelitian secara tatap muka terbatas dengan adanya system  jarak jauh yang dikuat kuasakan. Sebagai alternatif, penelitian dilakukan secara wawancara ditalian, video observasi, menggali informasi melalui akun youtube dan jaringan alam maya untuk mengumpulkan maklumat yang asli. Ianya di Analisa dengan triangulasi. Hasil dari penelitian, terdapat bimbingan pengajian agama dalam pendidikan rohani yang diutamakan untuk orang tua lansia dirumah kebajikan ini. Sejajar dengan Pendidikan agama, penjagaan lansia melalui psikologi yang mengarah kepada kesihatan dan kesejahteraan menjadi  misi dan visi, supaya dapat memberi menafaat kepada lansia dan tidak melahirkan isu-isu kebimbangan kepada masyarakat. Sebagai saranan, bimbingan agama perlu disentuh lebih banyak kepada ilmu ‘fiqh’ yang berkaitan dengan kehidupan harian selain dari membaca al-Quran sahaja. Mengggalakan lebih banyak berzikir supaya lansia dapat meningkatkan keimanan dengan lebih mendekati kepada Allah dan ini akan mendorong lansia lebih merasa tenang dan berdikari.